1981
DOI: 10.1051/rnd:19810301
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzymes in the germ-free animal

Abstract: Summary.The digestive physiology of the germ-free animal has a number of characteristics (cecal hypertrophy, slower small intestine cell renewal, slower gastric emptying and intestinal transit) which distinguish it from that of the conventional animal. If the germ-free model is to be used to determine the role of gastrointestinal microflora in the nutrition of the conventional animal, it is essential to complete the study of these characteristics by data on digestive enzymes in the germ-free. The present paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…It has been proposed that the underlying mechanisms for the growth promoting effect of antibiotics are related to interventions in the gastrointestinal tract and more particular in the small intestine, at the bacteriological, physiological and immunological level (Visek 1978, Vervaeke et al 1979, Corring et al 1981, Anderson et al 1999, Hillman 2001, Verstegen & Williams 2002, Gaskins et al 2002. Based on these considerations, several substances as possible alternatives for nutritional antibiotics have been put forward: probiotics, non-digestible oligosaccharides (NDO) with or without prebiotic properties, organic acids, enzymes (proteases, NSP-ases), herbs, bacteriocins, antimicrobial peptides and bacteriophages (Partanen & Mroz 1999, Hillman 2001, Dierick et al 2002Reid & Friendship 2002, Verstegen & Williams 2002, Joerger 2003, Ricke 2003, Montagne et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the underlying mechanisms for the growth promoting effect of antibiotics are related to interventions in the gastrointestinal tract and more particular in the small intestine, at the bacteriological, physiological and immunological level (Visek 1978, Vervaeke et al 1979, Corring et al 1981, Anderson et al 1999, Hillman 2001, Verstegen & Williams 2002, Gaskins et al 2002. Based on these considerations, several substances as possible alternatives for nutritional antibiotics have been put forward: probiotics, non-digestible oligosaccharides (NDO) with or without prebiotic properties, organic acids, enzymes (proteases, NSP-ases), herbs, bacteriocins, antimicrobial peptides and bacteriophages (Partanen & Mroz 1999, Hillman 2001, Dierick et al 2002Reid & Friendship 2002, Verstegen & Williams 2002, Joerger 2003, Ricke 2003, Montagne et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The large intestine of GF mice contains increased levels of digestive enzymes, the accumulation of which could also be responsible for the cecal dilatation [ 35 ]. Thus, we hypothesized that GF C3H mice in comparison with GF B6J mice show decreased levels of digestive enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, urinary ammonia dropped when sodium bicarbonate was included in the feed suggesting that acid:base balance may influence volatility of N in poultry waste streams. Corring et al (1981) reported that pancreatic and gastric output is similar in GF and CV animals but the absence of a microbiome in GF animals increases the persistency of endogenous enzyme activity in the intestine and loss of endogenous N from the gut. In CV animals more of the host-derived N is metabolized by bacteria and then either absorbed by the host where it is used to synthesize nonessential amino acids or is converted into microbial biomass.…”
Section: Protein Metabolism and Nitrogen Cyclingmentioning
confidence: 98%
“…These microbiome-related differences are particularly important for retention of unsaturated fatty acids such as palmitic and stearic whereas unsaturated fatty acids such as oleic or linoleic are less affected. Corring et al (1981) reported that bacterial hydrolases can split the bond between bile salts and taurine and glycine which is why GF animals have more primary, unmodified bile salts in the intestinal tract. Liver bile biosynthesis in GF animals is also lower than in CV animals and GF animals also have lower rates of catabolism of hepatic cholesterol, which explains the higher liver fat concentration in GF animals ( Furuse and Yokota, 1984a ).…”
Section: Energy Metabolism and Metabolic Ratementioning
confidence: 99%
See 1 more Smart Citation